2018
DOI: 10.1186/s12936-018-2326-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasmodium falciparum and Plasmodium vivax recent exposure in an area of significantly decreased transmission intensity in Central Vietnam

Abstract: BackgroundIn Vietnam, malaria transmission has been reduced to very low levels over the past 20 years, and as a consequence, the country aims to eliminate malaria by 2030. This study aimed to characterize the dynamics and extent of the parasite reservoir in Central Vietnam, in order to further target elimination strategies and surveillance.MethodsA 1-year prospective cohort study (n = 429) was performed in three rural communities in Quang Nam province. Six malaria screenings were conducted between November 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…In addition, it was reported that between 2006 and 2010, 70% of infections in Vietnam were due to P. falciparum . However, due to control measures, there has been a stronger impact on P. falciparum than on P. vivax since 2014, resulting in an almost equal ratio of both species [ 27 ]. Furthermore, co-infections with P. knowlesi and P. vivax have been documented in mosquitoes and humans in South Vietnam [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that between 2006 and 2010, 70% of infections in Vietnam were due to P. falciparum . However, due to control measures, there has been a stronger impact on P. falciparum than on P. vivax since 2014, resulting in an almost equal ratio of both species [ 27 ]. Furthermore, co-infections with P. knowlesi and P. vivax have been documented in mosquitoes and humans in South Vietnam [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such serological tools are of special interest in pre-elimination scenarios existing in Vietnam, with marked spatial transmission heterogeneity ( i.e. hotspots of transmission surrounded by areas of no transmission), where geographical stratification in transmission levels becomes essential to target NMCP interventions efficiently [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…<Day 28) (20,21,23), only one confirmed recurrent infections (n=3) with blood CQ concentration above MEC in Quang Nam in 2011 (20). Although the present study was conceived as a continuation of CQR monitoring in Quang Nam province (20), malaria cases rapidly decreased there after 2013, with mostly residual P. vivax by 2015, which was insufficient to conduct classical TES designs due to obvious time and logistic constraints (48). The primary endpoints presented in this study suggest CQ remained largely efficacious in Gia Lai province until 2017, with mostly late recurrences detected after Day 28 in the presence of blood CQ concentrations below MEC, similar to findings in the southern province of Binh Phuoc (22).…”
Section: Discussionmentioning
confidence: 99%